Patient autonomy in self-managing their bronchial asthma exacerbation and its associated factors, 2024 - Abdulwehab, Sadik; Kedir, Frezer (Frontiers in Allergy, 2024)
IntroductionAsthma, a global chronic respiratory condition, varies in patient autonomy due to limited resources, health literacy, and cultural beliefs, emphasizing the importance of understanding this autonomy for improved asthma management.MethodsA cross-sectional study was conducted at Jimma University Comprehensive Specialized Hospital, involving face-to-face interviews with 175 patients. Data was collected on sociodemographic characteristics, clinical factors, and autonomy levels using a validated Patient Autonomy Preference Index. Descriptive statistics and binary logistic regression analysis were used.ResultsA total of 175 participants were recruited, out of them 41.7% (95% CI: 31.19, 40.41)) of participants were autonomous in managing their asthma exacerbation. 127 (72.6%) of study participants were female, with a mean age of 47.51 (SD ± 13.96), 101(57.7%) were live in urban areas, 54 (30.9%) had no formal education, 140 (80%) were married, 112 (64%) had health insurance, and 102(83.3%) obtained health information about their condition from healthcare workers. Reside in an urban area (AOR = 3.24; 95% CI: 1.40–7.49, p < 0.006), have health insurance (AOR = 4.30; 95% CI: 1.76–10.51, p < 0.001), those doing regular exercise (AOR = 4.79; 95% CI: 1.69–13.64, p < 0.003), have family history (AOR = 7.47; 95% CI: 1.61–34.60, p < 0.01), have a duration above five years since diagnosis (AOR = 0.44; 95% CI: 1.04–1.26, p < 0.003), and participants with a high level of health literacy (AOR = 1.10; 95% CI: 1.00–1.20, p < 0.042) become associated with being autonomous in managing asthma exacerbation.Conclusion and recommendationOnly around forty-two percent of study participants were autonomous in managing their asthma exacerbation. Thus healthcare providers should give due attention to those who reside in rural areas, are not insured, recently diagnosed with asthma, and with low health literacy to enhance patient autonomy and self-management practices, ultimately improving health outcomes for individuals with asthma.